2007
DOI: 10.1007/s11748-007-0178-7
|View full text |Cite
|
Sign up to set email alerts
|

Simple surgical treatment for pleuroperitoneal communication without interruption of continuous ambulatory peritoneal dialysis

Abstract: Pleuroperitoneal communication is a complication of continuous ambulatory peritoneal dialysis (CAPD) that can necessitate cessation of CAPD. Hemodialysis was started on a 52-year-old woman and shifted to CAPD 1 month later. However, 18 days after initiation of CAPD, her chest radiograph showed a right-side hydrothorax. Thoracentesis yielded a colorless pleural effusion with markedly higher glucose levels than in her serum, indicating the presence of pleuroperitoneal communication. Three days later, thoracoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“… 8 , 11 13 , 29 Even restarting PD with low volumes on the operative day has been reported anecdotally. 30 On the other hand, one report has described the impact of gynecologic surgeries on the continuation of PD, reporting on 3 patients who underwent hysterectomy. All patients were shifted to HD in the immediate postoperative period, and PD was successfully restarted after 2 to 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 11 13 , 29 Even restarting PD with low volumes on the operative day has been reported anecdotally. 30 On the other hand, one report has described the impact of gynecologic surgeries on the continuation of PD, reporting on 3 patients who underwent hysterectomy. All patients were shifted to HD in the immediate postoperative period, and PD was successfully restarted after 2 to 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…One group advocates early diaphragmatic repair and continuation of peritoneal dialysis [12]. In this case, thorascopic diaphragmatic repair was performed using absorbable polyglycolic acid felt, and fibrin glue [12]. …”
Section: Discussionmentioning
confidence: 99%
“…We successfully treated hydrothorax with direct repair of the diaphragm perforation via video‐assisted thoracic surgery and concluded that direct repair was the best method to cure this problem 26 . Others have also had a similar experience 27,28 . Although the open method to repair the diaphragm 29 or pleurodesis have been applied, 25 we still regard video‐assisted thoracoscopic surgery repair as the best method.…”
Section: Discussionmentioning
confidence: 99%